Georges De Schrijver, S.J., Imagining the Creator God from Antiquity to Astrophysics - Suarez, V. Fullente (Archīum Ateneo, 2024)
Georges De Schrijver, S.J., Imagining the Creator God from Antiquity to Astrophysics